Perinatal outcome in twins. A hospital based comparative study at a single third-level care centre in Croatia - Dino Pavoković; Vesna Elveđi Gašparović; Tvrtko Tupek; Analena Gregorić; Ana Tikvica Luetić; Dubravko Habek (IMR Press, 2021)
Background: The goal of our study is to explore the association of assisted reproductive technology (ART) as contributing factor for obstetric complications and perinatal outcome in twin pregnancies during a 14-year period at a single tertiary centre. Methods: We collected the data (from maternal and neonatal medical records) from 731 twin pregnancies; 192 conceived by ART and 539 twin pregnancies conceived naturally during a 14-year period. Results: Pregnancy complications in twin pregnancies mainly included preterm premature rupture of membranes, gestational diabetes mellitus, and preeclampsia. Higher occurrence of placenta praevia in the ART group was the only perinatal risk related to twin pregnancies in the ART group as compared to those conceived naturally. Over 71% of ART twins were delivered by caesarean section, which is considerably increased as compared to non-ART twins (p = 0.042). Neonatal complications in both groups mainly included low Apgar score in the 1st minute, low birth weight and admission to NICU, and the incidences of these complications were comparable between the groups. Conclusion: Our results indicated that ART procedures were not followed by adverse obstetric and perinatal outcome in twin pregnancy delivered at single tertiary centre, except for the slightly higher risk of placenta praevia.